Controversy over the Existence of the World - Ingarden, Roman (Peter Lang International Academic Publishers, 2024)
Roman Ingarden (1893-1970), one of Husserl’s closest students and friends, ranks among the most eminent of the first generation of phenomenologists. His magisterial Controversy over the Existence of the World, written during the years of World War II in occupied Poland, consists of a fundamental defense of realism in phenomenology. Volume I, which receives here its first complete and critical translation into English, initiates the grand project of refuting transcendental idealism, and begins by setting the foundations for an elaborate and precise ontological system. This is Ingarden’s greatest accomplishment, who is rather known as a theoretician of literature than an ontologist outside of Poland. The most important achievement of Ingarden’s ontology is an analysis of the modes of being of various types of objects – things, processes, events, purely intentional objects and ideas. The three-volume Controversy is perhaps the last great systematic work in the history of philosophy, and undoubtedly one of the most important works in 20th century philosophical literature.